Adsorbed States of Hydrogen on Platinum: A New Perspective. Issue 26 (17th April 2019) - Parker, Stewart F.; Mukhopadhyay, Sanghamitra; Jiménez‐Ruiz, Mónica; Albers, Peter W.
Abstract: The interaction of hydrogen with platinum is enormously important in many areas of catalysis. The most significant of these are in polymer electrolyte membrane fuel cells (PEMFC), in which carbon‐supported platinum is used to dissociate hydrogen gas at the anode. The nature of adsorbed hydrogen on platinum has been studied for many years on single‐crystal surfaces, on high‐surface area‐platinum metal (Raney platinum and platinum black), and on supported catalysts. Many forms of vibrational spectroscopy have played a key role in these studies, however, there is still no clear consensus as to the assignment of the spectra. In this work, ab initio molecular dynamics (AIMD) and lattice dynamics were used to study a 1.1 nm nanoparticle, Pt44 H80 . The results were compared to new inelastic neutron scattering spectra of hydrogen on platinum black and of a carbon‐supported platinum fuel cell catalyst and an assignment scheme that rationalises all previous data is proposed. Abstract : The nature of adsorbed hydrogen on platinum has been studied for many years. It is shown that, contrary to the accepted understanding, the major species present is hydrogen in a twofold site.